Swift heavy ion irradiation-induced modifications in structural, magnetic and electrical transport properties of epitaxial magnetite thin films - SHVETS, IGOR (My University, 2006)
The effect of swift heavy ion SHI irradiation 190 MeV Ag on structural, electrical transport and magnetic properties of epitaxial magnetite Fe3O4 thin films thickness 70 nm grown on MgO 100 oriented substrate have been investigated. The x-ray diffraction shows that at low fluence values up to 5 1011 ions/cm2, the strain in the films is relaxed, whereas, at higher fluence range 1 1012?1 1013 ions/cm2, the epitaxial relationship with the substrate is lost along with a phase transformation from magnetite to more oxidized magnetite phase i.e., maghemite . The Verwey transition temperature measured by electrical transport is found to increase from 109 to 117 K with the low fluence SHI irradiation, which is related to the irradiation induced strain relaxation and structural modifications. At higher fluences the system did not show Verwey transition and the resistance is also increased. The similar results were obtained by magnetization studies. The observed magnetization at 1 T field is increased at low fluence suggesting the reduction of areas with frustrated exchange interactions associated with the cationic arrangement at the anti phase boundaries. At higher fluences it decreases monotonically, indicating the emergence of other phases. The observed modifications are explained on the basis of structural strain and disorder induced by swift heavy ions, which lead to modification of the interionic Coulomb potential at octahedral sublattices and bandwidth in this system.
PUBLISHED
Keywords: Atomic, molecular and chemical physics; thin films